A qualitative study of referring agents' perceptions of access barriers to inpatient substance abuse treatment centres in the Western Cape. Issue 1 (December 2015) - Isobell, Deborah; Kamaloodien, Kamal; Savahl, Shazly
Abstract Background Despite empirical support for the individual and public health benefits of treating substance use disorders (SUDs), access to these services is impeded by several barriers. Although many studies on access barriers have been put forward in the literature, few have explored the barriers to accessing state-funded inpatient substance abuse treatment or the views of referral agents. Methods A qualitative study was conducted to explore referring agents' perceptions of the barriers to accessing state-funded inpatient substance abuse treatment centres in the Western Cape Province of South Africa. Six individual in-depth interviews were conducted and analysed using theoretical thematic analysis. Results The key barriers to emerge from the analysis pertained to referring agents' perceptions of the following: service users, the substance abuse referral and treatment system and community dynamics. Conclusions Recommendations are made for interventions to address the identified barriers.